2021
DOI: 10.1186/s12886-021-01826-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ocular biometric measurements in patients with cataract using three swept-source optical coherence tomography devices

Abstract: Background Precise measurement of ocular biometry is critical for determining intraocular lens power. Newly developed swept-source optical coherence tomography (SS-OCT) - based ocular biometric devices, ANTERION and CASIA2 provide ocular biometric measurements as IOLMaster 700. This study aimed to assess agreement between three devices. Methods This retrospective comparative study includes patients with cataract who underwent ocular biometric measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 25 publications
(35 reference statements)
6
36
1
Order By: Relevance
“…However, concordance between the devices was high, with differences that were not clinically relevant in IOL calculation. Oh et al [ 16 ] reported mean difference of AL 0.005 mm, with ICC 0.999 in their study of 47 eyes of 29 patients. CCT, ACD and keratometry revealed excellent agreement as well.…”
Section: Discussionmentioning
confidence: 94%
“…However, concordance between the devices was high, with differences that were not clinically relevant in IOL calculation. Oh et al [ 16 ] reported mean difference of AL 0.005 mm, with ICC 0.999 in their study of 47 eyes of 29 patients. CCT, ACD and keratometry revealed excellent agreement as well.…”
Section: Discussionmentioning
confidence: 94%
“…As we all know, if a new device wants to be recognized by clinicians and be widely used in clinical practice, it will be compared with the currently recognized instrument. As far as we know, there are currently few studies comparing CASIA 2 with IOLMaster 700 in anterior segment parameter measurements (16,17). The sample size of our study (81 eyes of 81 patients) is larger than the previous study comparing CASIA2 and IOLMaster 700 (48 eyes of 48 patients and 47 eyes of 29 patients, respectively).…”
Section: Introductionmentioning
confidence: 77%
“…3 Oh et al reported excellent agreement for AL and anterior K but found no significant offset in ACD and LT in 29 patients. 7 Variations in ACD measurement contribute the most to errors in IOL power calculation, although substantial improvement has been achieved with modern biometers. 27 In accordance with previous findings, we measured a significantly deeper ACD with Biometer B for BUII, EVO 2.0, Haigis, Hoffer Q, Holladay 1, Kane, and SRK/T intraocular lens power calculation formulas.…”
Section: Accuracy Of Iol Power Calculationmentioning
confidence: 99%